Social capital, household income, and community development in Bhutan: a case study of a dairy cooperative. Issue 4 (18th May 2016) - Tenzin, Galey; Natsuda, Kaoru
ABSTRACT: Using a case of a dairy cooperative in Bhutan, this study investigates how social capital enhances individual household income and community development in rural areas. It also examines the influence of cooperatives in social capital formation. The study finds that social capital facilitates households that are resource-constrained by working together to reduce costs through economies of scale, enhancing information accessibility, building confidence, and strengthening teamwork. It fosters not only an improvement in the livelihoods of cooperative members, but also provides a positive influence for non-members and the community as a whole. The study also reveals that cooperatives influence formation of three forms of bonding, bridging, and linking social capitals. While bonding social capital facilitates strong teamwork among the members, bridging and linking social capitals connect the cooperatives with the outside networks and provides them more opportunities and services for its sustainability.